2005
DOI: 10.1021/bi050467s
|View full text |Cite
|
Sign up to set email alerts
|

Carbon-13 NMR Method for the Detection of Correlated Hydrogen Exchange at Adjacent Backbone Peptide Amides and Its Application to Hydrogen Exchange in Five Antiparallel β Strands within the Hydrophobic Core of Streptomyces Subtilisin Inhibitor (SSI)

Abstract: A novel method for monitoring proton-deuteron (H/D) exchange at backbone amides is based on the observation of H/D isotope effects on the 13 C NMR signals from peptide carbonyls. The line shape of the carbonyl 13 C i signal is influenced by differential H/D occupancy at the two adjacent amides: the H N i+1 (β-site) and the H N i (γ-site). At a carbon frequency of 75.4 MHz, the H→D isotope shifts on the 13 C signal are about 5-7 Hz for exchange at the β-site and 2 Hz or less for exchange at the γ-site. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…The carbonyl chemical shift is affected by deuterium substitution of its neighboring amide positions [86,87]. This deuterium-induced isotope shift on 13 C signals ($0.1 ppm) was observed even at 52°C for the H(C)CO peaks of the Fc dissolved in a buffer (pH 6.0) containing a 1:1 mixture of H 2 O and D 2 O, indicating a slow hydrogen-deuterium exchange of the acetamide groups (Fig.…”
Section: Local Structures and Dynamics Of Glycansmentioning
confidence: 93%
“…The carbonyl chemical shift is affected by deuterium substitution of its neighboring amide positions [86,87]. This deuterium-induced isotope shift on 13 C signals ($0.1 ppm) was observed even at 52°C for the H(C)CO peaks of the Fc dissolved in a buffer (pH 6.0) containing a 1:1 mixture of H 2 O and D 2 O, indicating a slow hydrogen-deuterium exchange of the acetamide groups (Fig.…”
Section: Local Structures and Dynamics Of Glycansmentioning
confidence: 93%
“…For instance, 1D difference NOE NMR on a partially exchanged sample (Wagner 1980; Roder et al 1985) indicated correlated exchange in the central part of an antiparallel β‐sheet in the bovine pancreatic trypsin inhibitor (BPTI), and H–D exchange monitored by mass spectroscopy revealed correlated exchange in lysozyme (Miranker et al 1993), in the native turkey ovomucoid third domain (Arrington et al 1999; Arrington and Robertson 2000) and in cytochrome c associated with negatively charged lipid membranes (Pinheiro et al 2000). Recently, Uchida et al (2005) reported an elegant method based on the observation of H/D isotope effects from neighboring amide hydrogens on the carbonyl 13 C chemical shift to detect correlated exchange, and applied it to the Streptomyces subtilisin inhibitor (SSI). In this method, the correlated exchange effects can be directly observed in 1D NMR spectra.…”
Section: Discussionmentioning
confidence: 99%
“…Approaching the EX1 limit to maximize the sensitivity of the observable k obs on these opening motions (see k op ), therefore, is a prerequisite for studies on the degree of correlation between the H–D exchange of neighboring amide protons. While local or global unfolding processes were shown to be involved in the mechanism of H–D exchange in various systems (Kim and Woodward 1993; Mayo and Baldwin 1993; Bai et al 1995; Loh et al 1996; Sivaraman et al 2001; Qu and Bolen 2003), correlated exchange of neighboring H N has rarely been demonstrated experimentally (Wagner 1980; Roder et al 1985; Pinheiro et al 2000; Uchida et al 2005).…”
mentioning
confidence: 99%
“…1,[19][20][21] In contrast to the 1 H detection experiments, the signal dispersion in the 13 C chemical shifts and the narrower linewidths are advantages of the 13 C direct observation approach for relatively large proteins. An NMR experiment using direct 13 C observation may also yield useful structural information, which cannot easily be obtained by the other methods.…”
Section: C/ 15 N Labelingmentioning
confidence: 99%